Transportation Applications of Solar Energy: Innovations and Consequences - Nishant Varshney (International Journal of Environmental Noise and Pollution Control, 2024)
The transportation industry is at the forefront of sustainability issues due to its substantial reliance on fossil fuels, which raises air pollution and greenhouse gas emissions. As a result, engineers and researchers have discovered that solar energy is a practical substitute for powering a variety of transportation vehicles. This study looks at the state of solar energy applications in the transportation industry today, exploring cutting-edge technologies, practical implementation issues, and the wider effects of widespread adoption. This paper clarifies the potential of solar-powered transportation to revolutionize mobility while mitigating environmental impacts through a systematic review of existing literature and case studies. Solar-powered cars, solar-integrated infrastructure, and new developments in market dynamics and policy are some of the major innovations that were covered. The article also examines the effects of switching to solar-powered transportation systems on the environment, society, and economy. This study advances sustainable transportation solutions by shedding light on the advantages as well as the difficulties.
Keywords: Consequences; Renewable energy; Solar Energy; Sustainability; innovations; solar-powered vehicles; transportation